Preliminary Study of Tsunami Impact on Soil Salinity for Agriculture Based on Geophysical Data, a Case Study of Aceh Besar, Indonesia - Muhammad Syukri; Sabrian Tri Anda; Rini Safitri; Zul Fadhli; Fiqa Miftahunnisa Hs (Malaysian Journal of Science, 2024)
The Tsunami, (natural phenomenon) that occurred in Aceh Province in 2004, not only caused severe damage to the infrastructure and human casualties but also altered the conditions of the soil. The change in soil condition led to economic loss (productivity and activity) in certain areas that were affected by the Tsunami. Studies show that the land inundated with Tsunami flood and sedimentation caused the land to become unproductive since the salinity level increased. The geophysical method was used to delineate the level of soil salinity in areas affected by Tsunami. A total of four measurement lines ranging in length from 160 to 210 meters were constructed specifically in Aceh Besar region. In the Blang Krueng District, three measuring lines (K1, K2, and K3) were positioned slightly away from the shoreline and one measurement line was conducted in the Blang Bintang (B1) region to validate the difference between the conductivity values of land polluted with tsunami sediment and seawater intrusion. Results show that the areas affected by Tsunami sedimentation had a greater conductivity value than unaffected areas classified by the conductivity value of 0.06 – 2 S/m and 0 – 0.05 S/m for Blang Krueng and Blang Bintang areas respectively.